Sense and sensibility - Austen, Jane, 1775-1817.; HarperCollins (London : HarperCollins, 2010)
Two sisters of opposing temperaments share the pangs of tragic love, and their mutual suffering brings a closer understanding between the two sisters, and true love finally triumphs.
Adult
Keywords: Sisters -- Fiction; Young women -- Fiction; Domestic fiction; Love stories; England -- Fiction